Hasil Belajar Siswa MAN 2 Medan Pada Materi Faktor Kemunduran Dinasti Abbasiyah (1000-1258M) dengan Strategi Cooperative Learning Type Student Teams Achievement Divisions (STAD) - Nunzairina Nunzairina; Eko Haris Alamsyah (JUSPI (Jurnal Sejarah Peradaban Islam), 2017)
This study aims to determine (1) Implementation of learning of Islamic History by subject decline of Abbasid dynasty through Strategy Learning Type Student Teams Achievement Divisions (STAD). (2) Increased student learning outcomes MAN 2 Medan through the implementation of Cooperative Learning Strategy Type Student Teams Achievement Divisions (STAD). This study is a classroom action research  (PTK) using 2 learning cycles. The research method aims to improve the quality of classroom learning practice. The main purpose of PTK is to solve real problems that occur in the classroom as well as seeking a scientific answer why it can be solved through the action to be taken. The research findings are: (1) Implementation of learning by using Cooperative Learning Type Student Teams Achievement Divisions (STAD) strategy is appropriate learning. (2) Increasing the average score since the preliminary test before the action is 71,5 with the completeness of 22%, the average value in cycle I is 77,4 with the completeness level 48%, the average value in cycle II is 86,6 with 100% completeness level, thus the learning outcomes of students from cycle I to cycle II has increased.Key  Word: STAD, Hasil Belajar Siswa, Materi Kemunduran Abbasiyah